2021
DOI: 10.1038/s41598-021-85062-3
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic dissection of down syndrome-associated alterations in APP/amyloid-β biology using mouse models

Abstract: Individuals who have Down syndrome (caused by trisomy of chromosome 21), have a greatly elevated risk of early-onset Alzheimer’s disease, in which amyloid-β accumulates in the brain. Amyloid-β is a product of the chromosome 21 gene APP (amyloid precursor protein) and the extra copy or ‘dose’ of APP is thought to be the cause of this early-onset Alzheimer’s disease. However, other chromosome 21 genes likely modulate disease when in three-copies in people with Down syndrome. Here we show that an extra copy of ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…App NL-F mouse model Following on from our previous studies, which indicated that an additional copy of Hsa21 alters APP biology and the accumulation of amyloid-β in vivo in an APP transgenic model [8,9], here we determined if an additional copy of Hsa21 modulated APP/amyloid-β biology in the App NL-F knock-in mouse model. We undertook a two generation cross of the Tc1 mouse model of DS [18], which contains a freely segregating copy of Hsa21 (but not a functional additional copy of APP) [23], with the App NL-F model to generate 4 genotypes of mice (wild-type, Tc1, App NL-F/NL-F and Tc1;App NL-F/NL-F ).…”
Section: Trisomy Of Chromosome 21 Decreases Accumulation Of Amyloid-β...mentioning
confidence: 99%
See 1 more Smart Citation
“…App NL-F mouse model Following on from our previous studies, which indicated that an additional copy of Hsa21 alters APP biology and the accumulation of amyloid-β in vivo in an APP transgenic model [8,9], here we determined if an additional copy of Hsa21 modulated APP/amyloid-β biology in the App NL-F knock-in mouse model. We undertook a two generation cross of the Tc1 mouse model of DS [18], which contains a freely segregating copy of Hsa21 (but not a functional additional copy of APP) [23], with the App NL-F model to generate 4 genotypes of mice (wild-type, Tc1, App NL-F/NL-F and Tc1;App NL-F/NL-F ).…”
Section: Trisomy Of Chromosome 21 Decreases Accumulation Of Amyloid-β...mentioning
confidence: 99%
“…The high prevalence of AD in DS is in part due to the gene encoding amyloid precursor protein (APP) being located on Hsa21, thereby raising APP and amyloid-β protein levels [4][5][6]. Recent studies in preclinical systems have demonstrated that an extra copy of other genes on Hsa21 can modulate APP biology [7][8][9][10] and thus may alter the earliest stages of AD in individuals who have DS. These extra genes may act to promote or to reduce amyloid-β accummulation and which mechanism predominates is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neurodevelopmental disorders discussed earlier in this review, Down syndrome (DS), which results from trisomy of human chromosome 21, is a cause of early onset Alzheimer's disease-dementia (AD-DS) (Ballard et al, 2016;Tosh et al, 2021). Two-thirds of individuals with DS will develop dementia by the age of 65 (Tosh et al, 2021).…”
Section: Additional Remarks: Vascular Deficits In Down Syndrome Traumatic Brain Injury and Depressionmentioning
confidence: 99%
“…In rodent studies of DS-AD, triplication of chromosome 21 genes other than APP demonstrated increased Aβ aggregation deposition and cognitive deficits (Wiseman et al, 2018). A recent study, focused on a model of DS comprising of a mutation in a Down syndrome critical region (Hsa21) on chromosome 21 encompassing 21q21-21q22.3 (Li et al, 2016;Tosh et al, 2021). This study crossed an Hsa21 mouse model of DS with partial trisomies other than APP with a transgenic APP mouse model and revealed that an additional copy of genes of the Hsa21 region modulates APP/Aβ biology, including Aβ aggregation and mortality (Tosh et al, 2021).…”
Section: Additional Remarks: Vascular Deficits In Down Syndrome Traumatic Brain Injury and Depressionmentioning
confidence: 99%
See 1 more Smart Citation